Development of Biotechnological Photosensitizers for Photodynamic Therapy: Cancer Research and Treatment—From Benchtop to Clinical Practice - Aires-Fernandes, Mariza [UNESP]; Botelho Costa, Ramon [UNESP]; Rochetti do Amaral, Stéphanie [UNESP]; Mussagy, Cassamo Ussemane; Santos-Ebinuma, Valéria C. [UNESP]; Primo, Fernando Lucas [UNESP] (My University, 2022)
Photodynamic therapy (PDT) is a noninvasive therapeutic approach that has been applied in studies for the treatment of various diseases. In this context, PDT has been suggested as a new therapy or adjuvant therapy to traditional cancer therapy. The mode of action of PDT consists of the generation of singlet oxygen (¹O2) and reactive oxygen species (ROS) through the administration of a compound called photosensitizer (PS), a light source, and molecular oxygen (3O2). This combination generates controlled photochemical reactions (photodynamic mechanisms) that produce ROS, such as singlet oxygen (¹O2), which can induce apoptosis and/or cell death induced by necrosis, degeneration of the tumor vasculature, stimulation of the antitumor immune response, and induction of inflammatory reactions in the illuminated region. However, the traditional compounds used in PDT limit its application. In this context, compounds of biotechnological origin with photosensitizing activity in association with nanotechnology are being used in PDT, aiming at its application in several types of cancer but with less toxicity toward neighboring tissues and better absorption of light for more aggressive types of cancer. In this review, we present studies involving innovatively developed PS that aimed to improve the efficiency of PDT in cancer treatment. Specifically, we focused on the clinical translation and application of PS of natural origin on cancer.
Keywords: biotechnological photosensitizers; cancer therapy; malignant tumors; nanobiotechnology; photodynamic therapy